Ultra‐Wide Vis–NIR Mg2Al4Si5O18:Eu2+, Cr3+ Phosphor Containing Unusual NIR Luminescence Induced by Cr3+ Occupying Tetrahedral Coordination for Hyperspectral Imaging. Issue 19 (14th July 2022) - Zou, Xikun; Zhang, Haoran; Li, Wei; Zheng, Mingtao; Molokeev, Maxim S.; Xia, Zhiguo; Zheng, Yinjian; Li, Qingming; Liu, Yingliang; Zhang, Xuejie; Lei, Bingfu
Abstract: Cr 3+ ‐activated broadband near‐infrared (NIR) phosphors, featured by the octahedral coordination preference and strong absorption in visible (Vis) region, have great potential application in nondestructive assessment. It is still a challenge to develop Cr 3+ ‐doped phosphors with the tetrahedrally coordinated Cr 3+ NIR emission behavior and ultra‐wide Vis–NIR luminescence. Herein, an unusual NIR‐emitting Mg2 Al4 Si5 O18 :Cr 3+ phosphor offers emission peak at 867 nm with full‐width at half‐maximum of 237 nm due to preferential occupation of the AlO4 tetrahedra by Cr 3+ as demonstrated by structural and optical properties studies. Eu 2+ –Cr 3+ energy transfer is proposed to induce ultra‐wide Vis–NIR Mg2 Al4 Si5 O18 :Eu 2+, Cr 3+ phosphors with more efficient NIR emission and lower thermal quenching behavior of Cr 3+ . The fabricated Vis–NIR phosphor‐converted light‐emitting diode is expected to be an alternative to halogen lamp in hyperspectral imaging. This work reveals the luminescence behavior of Cr 3+ in tetrahedra and demonstrates the application of Mg2 Al4 Si5 O18 :Eu 2+, Cr 3+ phosphor in hyperspectral imaging, which will facilitate further research on NIR and Vis–NIR phosphors. Abstract : An ultra‐wide visible–near‐infrared emitting Mg2 Al4 Si5 O18 :Eu 2+, Cr 3+ phosphor is obtained by constructing efficient Eu 2+ –Cr 3+ energy transfer, where the visible emission is ascribed to the Eu 2+ dopants inserting the sixfold coordinated vacant channel via the glass crystallization, and the unusual near‐infrared luminescence is derived from Cr 3+ ions preferentially occupying the Al1O4 and Al2O4 tetrahedra.